A novel strategy for enhancing the thermal conductivity of shape-stable phase change materials via carbon-based in situ reduction of metal ions. (10th January 2020) - Chen, Yan; Ding, Han; Gao, Junkai; Tang, Xi; Liu, Yi; Yang, Mouyuan
Abstract: A novel and efficient strategy was developed for increasing the thermal conductivity of shape-stable phase change materials (ss-PCMs) using in situ reduction of copper ions, and this strategy used carbon-based adsorbents to adsorb and reduce Cu 2+ to form copper microspheres (CMSs) on the surface of the adsorbents, which were then used as the matrix of polyethylene glycol (PEG). Jujube pit biochar (JPB), which was prepared from forestry and agricultural residues of jujube pit by a simple pyrolysis method, was used as the carbon-based adsorbent. The study results demonstrated that the thermal conductivity of jujube pit biochar-based ss-PCMs of PEG/CMS-JPB was 0.630 W/m K, which is a 125% increase over the value of PEG (0.280 W/m K), and PEG/CMS-JPB possessed a favourable phase change enthalpy of 108.2 J/g. Additionally, according to the thermogravimetric analysis (TGA), Fourier transform infrared (FT-IR), and X-ray diffraction (XRD) results, PEG/CMS-JPB possessed excellent thermal stability and had good chemical compatibility between PEG and the carrier. Therefore, the jujube pit biochar that was prepared using agricultural waste could be used as a favourable carrier in the preparation of ss-PCMs, and more importantly, this paper provides a new general approach for improving the thermal conductivity of ss-PCMs. Graphical abstract: Image 1 Highlights: Copper microspheres (CMSs) were prepared using a carbon-based in situ reduction method. The thermal conductivity of the phase change material (PCM) was enhanced effectively using CMSs. A novel strategy for improving the thermal conductivity of PCM was developed. The preparation of CMSs was easy-to-operate.